The Developments of Customary Marine Rights A Case Study in Kei Islands, Southeast Maluku Regency - Sri Ayu Aniningsih (Journal of Wetlands Environmental Management, 2014)
This study is aimed to describe the developments  and  design a concept of recognition of customary marine rights in future in Kei  Islands. The method of this study is juridical empirical and the specification of it is descriptive analytical. The data consists of primary data and secondary data. It is analyzed by qualitative method. This study results that  the developments of customary marine rights include only in norms as a translation of customary law  principles. The developments of it occur in legal subject and legal object of customary marine rights, traditional institutional structure and the customary law of Kei people. There are many factors that influence the developments of customary marine rights such as economic, social, cultural, and political factors. The principles of customary marine rights in Kei Islands  are : (a). basically the using customary  marine rights just for Kei people, but foreigners can use them too if  knowledge of head of village; (b). communal;  (c). religious-magical;  (d). the highest authority in the head of village; (e).basically the using of customary marine rights only to fulfill the needs of daily living; (f). the using of rights that must be based on customary law. The concept of recognition for customary marine rights in Kei Islands in the future includes the existence legal subjects, legal objects, customary law and the functioning of the traditional institutional structure.